Invertebrate recognition protein cross-reacts with an immunoglobulin idiotype (The Rockefeller University Press, 1984)
To estimate the minimal structural requirements for cross-reaction of idiotypic determinants, we determined the capacity of monoclonal antibodies specific for the idiotype of the phosphorylcholine (PC)- binding myeloma protein TEPC-15 for cross-reactivities with the PC- binding, acute-phase protein C-reactive protein (CRP) and the hemagglutinin from the horseshoe crab Limulus polyphemus (limulin), which binds sialic acid and PC. Certain monoclonal antibodies (MAb) to the TEPC-15 idiotype showed strong cross-reactions with CRP and limulin when tested by enzyme-linked immunoadsorbent assays. The specificity of the cross-reactivities was confirmed by testing the binding of the reactive anti-TEPC-15 MAb to both CRP and limulin in the presence of p- nitrophenylphosphorylcholine (pNPPC), N-acetylneuraminic acid, and bovine submaxillary mucin. The binding of the MAb to both CRP and limulin was strongly decreased by pNPPC, partially decreased by free PC, and not affected by N-acetylneuraminic acid or bovine submaxillary mucin. Neither CRP nor limulin showed significant overall sequence homology to vertebrate immunoglobulins. However, CRP, limulin, and TEPC- 15 variable region heavy chain (VH) shared short stretches of homology (8-10 amino acids) that mapped to a stretch comprised of the second complementarity determining region and third framework region of the TEPC-15 VH. These results might reflect either evolutionary convergence forced upon molecules of diverse evolutionary histories because of steric requirements of binding the same ligand, or a conservation of primitive combining site gene segments in evolution.